Fast pyrolysis of biomass: A review of relevant aspects. Part I: Parametric study (2015)
Recent years have witnessed a growing interest in developing biofuels from biomass by thermochemical processes like fast pyrolysis as a promising alternative to supply ever-growing energy consumption. However, the fast pyrolysis process is complex, involving changes in phase, mass, energy, and momentum transport phenomena which are all strongly coupled with the reaction rate. Despite many studies in the area, there is no agreement in the literature regarding the reaction mechanisms. Furthermore, no detailed universally applicable phenomenological models have been proposed to describe the main physical and chemical processes occurring within a particle of biomass. This has led to difficulties in reactor design and pilot industrial scale operation, stunting the popularization of the technology. This paper reviews relevant topics to help researchers gain a better understanding of how to address the modeling of biomass pyrolysis.